Personalbedarfsermittlung für eine leitliniengerechte stationäre Qualifizierte Entzugsbehandlung bei Alkoholabhängigkeit = Normative definition of staff requirement for a guideline-adherent inpatient qualified detoxification treatment in alcoholdependence - Kiefer, Falk; Koopmann, Anne; Godemann, Frank; Wolff, J.; Batra, Anil; Mann, Karl (Der Nervenarzt, 2016)
The central element of the “qualified withdrawal treatment” of alcohol dependence is - in addition to physical withdrawal treatment - psychotherapy. The treatment of the underlying addictive disorder that is displayed by intoxication, harmful behaviour and withdrawal symptoms is only possible with a combination of somatic and psychotherapeutic treatment elements. The successfully established multimodal therapy of the “qualified alcohol withdrawal treatment”, postulated in the current S3-Treatment Guidelines, requires a multi-disciplinary treatment team with psychotherapeutic competence. The aim of the present work is to calculate the normative staff requirement of a guideline-based 21-day qualified withdrawal treatment and to compare the result with the staffing regulations of the German Institute for Hospital Reimbursement. The present data support the hypothesis that even in the case of a hundred per cent implementation of these data, adequate therapy of alcohol-related disorders, according to the guidelines, is not feasible. This has to be considered when further developing the finance compensation system based on the described superseded elements of the German Institute for Hospital Reimbursement.
Gesehen am 28.02.2019